Late lexical insertion in verbal agreement and in split interrogatives - Fábregas, Antonio (Círculo de Lingüística Aplicada a la Comunicación, 2012)
This article addresses the problem of how lexicon and grammar interact with each other. Through the study of two empirical cases we argue for a late insertion account in which items are introduced to spell out grammatical constructions without the intermediation of additional levels of operations. We argue that data like those are best handled by a system like that, to the extent that no additional assumptions have to be made. The two phenomena studied are the bound variable reading of first and second person pronouns and qué-extension in the colloquial Peninsular Spanish variety..
Keywords: lexicon; grammar; late insertion; split questions; bound variable readings